Schools as potential risk sites for vector-borne disease transmission: Mosquito vectors in rural schools in two municipalities in Colombia (2015)
Dengue and other vector-borne diseases are of great public health importance in Colombia. Vector surveillance and control activities are often focused at the household level. Little is known about the importance of nonhousehold sites, including schools, in maintaining vector-borne disease transmission. The objectives of this paper were to determine the mosquito species composition in rural schools in 2 municipalities in Colombia and to assess the potential risk of vector-borne disease transmission in school settings. Entomological surveys were carried out in rural schools during the dry and rainy seasons of 2011. A total of 12 mosquito species were found: Aedes aegypti, Anopheles pseudopunctipennis, Culex coronator, Cx. quinquefasciatus, and Limatus durhamii in both immature and adult forms; Ae. fluviatilis, Cx. nigripalpus, Cx. corniger, and Psorophora ferox in immature forms only; and Ae. angustivittatus, Haemagogus equinus, and Trichoprosopon lampropus in adult forms only. The most common mosquito species was Cx. quinquefasciatus. Classrooms contained the greatest abundance of adult female Ae. aegypti and Cx. quinquefasciatus. The most common Ae. aegypti breeding sites were containers classified as "others" (e.g., cans), followed by containers used for water storage. A high level of Ae. aegypti infestation was found during the wet season. Our results suggest that rural schools are potentially important foci for the transmission of dengue and other mosquito-borne diseases. We propose that public health programs should be implemented in rural schools to prevent vector-borne diseases.